(3GdChRGf aj Yde GdejRGfs - (3CHh eSdeI eMeO Hf EHQGgje Hf YHO GdOGFe GdeSdej GdeLQjWjs
(3ChdgG (B:s
(3hHYO bGd GdYHO GdabjQ bQCJ hJageJ Yde Gdhdjf ahLOJ LejY eGfGdhg ai ReGfge s
(3BNQgG (B:s
(3bGd Gddg JYGdi hgh CUOb GdbGFdjf (B((3hGdPjf LGgOhG ajfG dfgOjfge SHdfG hEf Gddg deY GdeMSfjf(B) (3JeJ GdYfGUQ HMeO Gddg s
(3HChdgG Jedc HNW GdTjN MSf GdLHQJi GdMfai hJedcGJ CNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B14 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYjGJ (B4) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdcjejGA h GdWHjYjGJs